2021
DOI: 10.3390/foods10112825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steam and Smoke Cooking Processes on Web-Foot Octopus (Amphioctopus sp.) Home Meal Replacement Product

Abstract: In Korea, the web-foot octopus (Amphioctopus sp.) is commonly consumed as jjukkumi bokkeum, a spicy stir-fried octopus dish. Using steaming and smoking methods, we made jjukkumi bokkeum home meal replacement (HMR) products. The response surface methodology (RSM) was employed to optimize the steam and smoke processes. Quick freezing was applied to freeze the test product at −35 °C. Then, the physicochemical, biological, nutritional characteristics, and shelf-life of the test HMR products were evaluated. The opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Among these, Sutikno et al [33] studied the development of HMR products using a mollusk, namely, web-foot octopus (Amphioctopus sp. ), Negara et al [34] focused on improving quality characteristics of HMR products using common squid (Todarodes pacificus Steenstrup), Kang et al [17] studied texture-modified octopus (Octopus vulgaris) arms, and Kang et al [35] conducted a study on the development of an elderly-friendly HMR product using common squid (Todarodes pacificus). However, to date, no studies have reported the development of a Jangjorim prototype using the long-arm octopus (Octopus minor); therefore, it was developed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, Sutikno et al [33] studied the development of HMR products using a mollusk, namely, web-foot octopus (Amphioctopus sp. ), Negara et al [34] focused on improving quality characteristics of HMR products using common squid (Todarodes pacificus Steenstrup), Kang et al [17] studied texture-modified octopus (Octopus vulgaris) arms, and Kang et al [35] conducted a study on the development of an elderly-friendly HMR product using common squid (Todarodes pacificus). However, to date, no studies have reported the development of a Jangjorim prototype using the long-arm octopus (Octopus minor); therefore, it was developed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Considering some of the most popular foods worldwide, it is now necessary to develop new processed seafood preparations that meet the preferences of elderly consumers. On the other hand, home meal replacement using webfoot octopus and squid [ 19 , 20 ] and elderly-friendly processed seafood products using pollack, halibut, mackerel, seaweed, and abalone have been developed. However, no studies have been conducted on the development of products such as convenience food or senior-friendly food using octopus.…”
Section: Introductionmentioning
confidence: 99%